Practices and Knowledge about Safe Pesticide use- a Cross sectional Study amongst Farmers of a district in Odisha, India - Senapati, Tapas Ranjan; Mohapatra, Ipsa; Behera, Basanta Kumar; Nayak, Smruti Ranjan; Kar, Ansuman; Panda, Prem Sagar (Indian Journal of Community Health, 2025)
Background: With agriculture being the second largest workforce sector in the world, the knowledge and practices on safe pesticide use among farmers is of paramount importance. Aim & Objectives: The study aimed to investigate the farmers’ knowledge and practices on safe use of pesticides. Methodology: A community based cross-sectional study was conducted among 421 farmers from December 2020 to September 2022 in the second populous district of the state. Data was collected using a semi structured questionnaire using demographic and occupational data, knowledge & practices on safe pesticide use. Data was entered into Microsoft excel and analysed using Epi Info statistical software. All categorical data was presented using frequency and percentages & continuous data in mean±SD. Results: The mean age was 40.53±6.7 years (18 to 65 years). Maximum (62.94%) were in the age-group of 40-60 years; 83.37 % were males and 79.33% literate. All the farmers used pesticides, 47.50% of them had an experience of >15 years in farming and 68.65% were using pesticides since 5-15 years. The overall knowledge was poor (68.4%).Conclusion: The overall knowledge on safe use of pesticides was poor, their practices still poorer. Most of them had not attended any training on integrated pest management.